Isomerization and Evaporation of Red Sorghum Hydrolyzate Sugar into Fructose Syrup through Water and Ethanol-Water as the Media - Permanasari, Ayu Ratna; Yulistiani, Yulistiani; Gustaji, F; Karisma, R F; Wibisono, Wahyu (Jurnal Internasional Penelitian Teknologi Terapan, 2020)
Red sorghum flour has considerable potential to be used as fructose syrup. The process of making fructose syrup was started with making hydrolyzate sugar by enzymatic hydrolysis of the polysaccharide into glucose syrup, then being isomerized using glucose-isomerase into fructose syrup. The study aimed to determine the best temperature in the isomerization process of hydrolyzate sugar from red sorghum flour through water and ethanol-water as the media and determine the optimum temperature of evaporation process to produce fructose syrup appropriate with SNI and HFS 42 commercials products. Isomerization was carried out on water media and ethanol-water media (2.5: 1) with temperature variations of 27 °C, 40 °C and 60 °C, with a total volume of 100 mL, for 43 hours, and enzyme concentration 1% (b/v) while the evaporation process was carried out at a pressure of 0.8 atm with a temperature variations of 55 °C, 60 °C, 75 °C, and a total volume of 30 ml. The best results of the isomerization process was obtained at 60 °C by water media with the concentration of fructose of 71.60 g/L and the evaporation process at 60 °C obtained an increase in fructose concentration by 70 % from initial fructose concentration and viscosity of 1.60 poise.